Bamboo (Poales, Poaceae): An Important Maintainer of Immature Mosquitoes (Diptera: Culicidae) in a Biodiversity Hotspot in the City of Rio de Janeiro, Brazil - Manuella Pereira Cerqueira Leite; Rayane Dias; Paulo José Leite; Shayenne Olsson Freitas Silva; Hélcio Reinaldo Gil-Santana; Roger Pimentel Barbosa; Cecilia Ferreira de Mello; Jeronimo Alencar (Life, 2024)
Although tropical forests are home to most of the global diversity, they suffer from the most significant knowledge gaps concerning their fauna. Despite its high biodiversity, Brazil is facing an alarming destruction of habitats, with species becoming extinct before they can be discovered or described via science. Therefore, there is an urgent need to expand wildlife inventories, including entomofauna surveys. The present study aimed to analyze the bionomic aspects and the influence of abiotic factors on mosquito fauna whose immature phases develop in two bamboo species, Guadua tagoara and Bambusa vulgaris, in Tijuca National Park, Rio de Janeiro, Brazil. Immatures were collected in 10 artificially drilled bamboo plants, in five stalk internodes per plant, at two sampling points, from March 2022 to March 2023, during 23 collections. A total of 1845 immatures were obtained, 72.14% at sampling point 1 and 27.86% at sampling point 2. Of this, 1162 individuals reached adulthood, belonging to the following species: Culex iridescens, Culex neglectus, Haemagogus leucocelaenus, Orthopodomyia albicosta, Sabethes identicus, Sabethes melanonymphe, Sabethes purpureus, Toxorhynchites bambusicola, Toxorhynchites sp., Trichoprosopon compressum, Trichoprosopon pallidiventer, Wyeomyia arthrostigma, Wyeomyia codiocampa, Wyeomyia lutzi, Wyeomyia oblita, Wyeomyia personata, Wyeomyia serrata, and Wyeomyia sp. The Tijuca National Park is a tourist spot and receives a large number of visitors. Thus, humans can become an accessible food source for mosquitoes in this area, making the species survey critical since important arbovirus vectors have been recorded in Rio de Janeiro.